Paulson's gift - Veronesi, Pietro; Zingales, Luigi (Journal of Financial Economics, 2010)
We calculate the costs and benefits of the largest ever US government intervention in the financial sector announced during the 2008 Columbus-day weekend. We estimate that this intervention increased the value of banks’ financial claims by 130 billion (bn) at a taxpayers’ cost of 21–44 billion with a net benefit between 86 and $109bn. By looking at the limited cross section, we infer that this net benefit arises from a reduction in the probability of bankruptcy, which we estimate would destroy 22% of the enterprise value. The big winners of the plan were the bondholders of the three former investment banks and Citigroup, while the losers were JP Morgan shareholders and the US taxpayers.